Zeolite-loaded regenerated cellulose aerogel hemostatic material and preparation method thereof

By dissolving carboxymethylated cellulose and polyethylene glycol under alkaline conditions, the zeolite-loaded regenerated cellulose aerogel is formed, which solves the thermal damage and tissue inflammation of zeolite hemostasis materials during application, and achieves efficient hemostasis and biosecurity.

CN119161628AActive Publication Date: 2024-12-20THE SECOND AFFILIATED HOSPITAL OF NAVAL MEDICAL UNIVERSITY PLA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411689137.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-20
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Existing zeolite hemostatic materials are prone to thermal damage and tissue inflammation when used, and their hemostatic efficacy decreases, making it difficult to maintain the close bond between the zeolite and the material, resulting in thermal damage and thrombosis.

Method used

Carboxymethylated cellulose and polyethylene glycol are dissolved in alkali solution, and zeolite is added to form a stable zeolite-regenerated cellulose homogenate, and fiber regeneration is carried out in an acid/alcohol solidification bath to form a zeolite-loaded regenerated cellulose. Aerogel, a three-dimensional network structure is formed by hydrogen bond recombination, and zeolite is uniformly loaded, and hemostatic material is prepared by freeze-dried.

Benefits of technology

The stable combination of zeolite and material is achieved, exothermic reaction is reduced, hemostatic performance is improved, thermal damage and tissue inflammation is avoided, and the effect of rapid adsorption of blood and stimulating coagulation is also safe and operational.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161628A_ABST
    Figure CN119161628A_ABST
Patent Text Reader

Abstract

The invention is applicable to the technical field of hemostatic materials, and provides a preparation method of a zeolite-loaded regenerated cellulose aerogel hemostatic material, which comprises the following steps: dissolving carboxymethylated cellulose and polyethylene glycol in an alkali solution to obtain a cellulose regeneration solution, then adding zeolite, and uniformly stirring to obtain a zeolite-loaded regenerated cellulose aerogel hemostatic material; white stable zeolite-regenerated cellulose homogenate is obtained; placing the zeolite-regenerated cellulose homogenate in an acid / alcohol coagulating bath for fiber regeneration to obtain zeolite-regenerated cellulose hydrogel; dialyzing the zeolite-regenerated cellulose hydrogel until the zeolite-regenerated cellulose hydrogel is neutral, removing salt, and freeze-drying to obtain the zeolite-loaded regenerated cellulose aerogel hemostatic material. The embodiment of the invention also provides the zeolite-loaded regenerated cellulose aerogel hemostatic material. The hemostatic material prepared by the invention has the advantages of high hemostatic speed, mild exothermic reaction, biological safety and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hemostatic materials, and in particular relates to a zeolite-loaded regenerated cellulose aerogel hemostatic material and a preparation method thereof. Background Art

[0002] Excessive blood loss is one of the main causes of death from trauma, and uncontrolled wound infection can also endanger life safety. The first 10 minutes after trauma is the key to first aid and improving the success rate of rescue. The body's own hemostasis mechanism is a complex and time-consuming process. When traumatic hemorrhage occurs, it is difficult to stop bleeding quickly by relying solely on the body itself. External intervention is required on the wound, that is, the use of hemostatic materials to achieve the purpose of rapid hemostasis. For ideal hemostatic materials, hemostatic effect, biocompatibility, safety and operability are essential parameters.

[0003] At present, the commonly used hemostatic materials mainly include chitosan, cellulose, sodium alginate, new polymers, etc. Organic and mineral hemostatic materials include zeolite, kaolin, silica, etc. Among them, zeolite is one of the classic hemostatic agents and has been widely used since it was approved by the FDA in 2002. It has the characteristics of rapid absorption of water. After contacting the wound, it can quickly absorb plasma, enrich blood cells and other components to achieve the purpose of rapid control of bleeding; at the same time, the inert composition of zeolite will not cause toxicity to the organism, but the use of exposed zeolite will cause severe thermal damage and necrosis of surrounding tissues. In the prior art, prehydrated zeolite hemostatic materials (ACS+) have been developed, which can produce less exothermic reactions and reduce thermal damage, but the hemostatic efficacy will decrease, and the tissue temperature of the wound will still rise to 50°C; at the same time, there is only physical adsorption between zeolite and the material, and the two are not tightly combined. Zeolite is not biodegradable, and it is easy to scatter on the wound during the hemostasis process and is not easy to remove, resulting in tissue inflammation and thrombosis.

[0004] Therefore, it is of great research significance to reduce the reaction heat of zeolite absorbing water and improve the stability of the combination of zeolite and materials without reducing the hemostatic effect. Summary of the invention

[0005] The purpose of the embodiments of the present invention is to provide a method for preparing a zeolite-loaded regenerated cellulose aerogel hemostatic material, aiming to solve the problems raised in the above-mentioned background technology.

[0006] The embodiment of the present invention is implemented as follows: a method for preparing a zeolite-loaded regenerated cellulose aerogel hemostatic material comprises the following steps: Dissolving carboxymethyl cellulose and polyethylene glycol in an alkaline solution to obtain a cellulose regeneration solution, then adding zeolite and stirring evenly to obtain a white stable zeolite-regenerated cellulose slurry; Placing the zeolite-cellulose regenerated cellulose homogenate in an acid / alcohol coagulation bath for fiber regeneration to obtain a zeolite-regenerated cellulose hydrogel, wherein the acid / alcohol coagulation bath is a mixture of an acid solution and an alcohol, wherein the acid solution is 10% sulfuric acid by mass, the alcohol is 50% ethanol by mass, and the mass ratio of the acid solution to the alcohol is 8:92; The zeolite-regenerated cellulose hydrogel was dialyzed to neutrality and the salt was removed, and then freeze-dried to obtain the zeolite-loaded regenerated cellulose aerogel hemostatic material.

[0007] Preferably, the carboxymethyl substitution degree of the carboxymethylated cellulose is 0.10-0.50.

[0008] Preferably, the alkaline solution is sodium hydroxide or potassium hydroxide.

[0009] Preferably, the mass concentration of carboxymethyl cellulose in the cellulose regeneration solution is 3-10%.

[0010] Preferably, the mass concentration of polyethylene glycol in the cellulose regeneration solution is 0.5-2%.

[0011] Preferably, the mass ratio of the zeolite to the carboxymethyl cellulose is 3-14:20.

[0012] Preferably, the dialysis is performed by washing with ultrapure water or ethanol.

[0013] Another object of the embodiment of the present invention is to provide a zeolite-loaded regenerated cellulose aerogel hemostatic material, which is prepared by the above-mentioned preparation method.

[0014] The embodiment of the present invention provides a method for preparing a zeolite-loaded regenerated cellulose aerogel hemostatic material, which utilizes high molecular weight carboxymethyl cellulose to destroy hydrogen bond interactions and dissolve under alkaline conditions, and is blended with zeolite to form a stable homogenate, and the fibers are regenerated by hydrogen bonds in a coagulation bath system to form a three-dimensional network structure of a hydrogel, and the cations in the zeolite are chelated by the carboxyl groups of the carboxymethyl groups, so that the zeolite is evenly loaded between the fibers, and freeze-dried to form a zeolite-loaded regenerated cellulose aerogel material; Compared with traditional zeolite-based hemostatic materials, the embodiments of the present invention form regenerated fiber aerogel materials through green solvents. Zeolite is stably combined in the three-dimensional structure of aerogel and has excellent hemostatic performance. Its hemostatic mechanism includes: physical adsorption. When aerogel acts on the bleeding site, it can quickly adsorb liquid components in the blood and enrich blood cells and other components on the interface; interface stimulation. The electric potential carried by zeolite can stimulate blood cells to trigger the coagulation cascade reaction; thermal stimulation: the three-dimensional structure of aerogel can quickly disperse the heat generated by zeolite to prevent the occurrence of thermal damage. At the same time, this heat can enhance platelet function. The hemostatic material has the advantages of fast hemostasis, mild exothermic reaction, and biosafety. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a photo of the zeolite-loaded regenerated cellulose aerogel hemostatic material provided in Example 1 of the present invention; Figure 2 This is a SEM image of the zeolite-loaded regenerated cellulose aerogel hemostatic material provided in Example 1 of the present invention (the left side is a cross-sectional scanning electron microscope image, and the right side is a surface scanning electron microscope image); Figure 3 The in vitro coagulation performance evaluation results of the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Examples 1-3 of the present invention (the left side is a data bar graph, and the right side is a physical display diagram); Figure 4 The blood compatibility test results of the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Example 1 of the present invention (the illustration is a real-life display); Figure 5 This is a graph showing the heat release evaluation during the in vivo hemostasis process of the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Example 1 of the present invention; Figure 6 This is the in vivo hemostatic performance evaluation result of the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0017] A method for preparing a zeolite-loaded regenerated cellulose aerogel hemostatic material comprises the following steps: (1) dissolving carboxymethyl cellulose and polyethylene glycol in an alkaline solution to obtain a cellulose regeneration solution, then adding zeolite and stirring evenly to obtain a white stable zeolite-regenerated cellulose slurry; (2) placing the zeolite-regenerated cellulose homogenate in an acid / alcohol coagulation bath of a certain concentration for fiber regeneration to obtain a zeolite-regenerated cellulose hydrogel, wherein the acid / alcohol coagulation bath is a mixture of an acid solution and an alcohol, wherein the acid solution is 10% sulfuric acid by mass, and the alcohol is 50% ethanol by mass, and the mass ratio of the acid solution to the alcohol is 8:92; (3) The zeolite-regenerated cellulose hydrogel was dialyzed to neutrality and the salt was removed, and then freeze-dried to obtain the zeolite-loaded regenerated cellulose aerogel hemostatic material, which was then frozen by liquid nitrogen to make its structure more compact; Wherein, the degree of substitution of the carboxymethyl cellulose is 0.10-0.50, preferably 0.16; the mass concentration of the carboxymethyl cellulose is 3-10%, preferably 7%; the alkaline solution includes but is not limited to sodium hydroxide and potassium hydroxide, preferably sodium hydroxide; The mass concentration of the polyethylene glycol is 0.5%-2%, preferably 1.5%; The mass ratio of the zeolite to the carboxymethyl cellulose is 3-14:20, preferably 3:20; The dialysis method is ultrapure water washing or ethanol washing, preferably ultrapure water washing.

[0018] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0019] The zeolite used in the embodiment of the present invention was purchased from Taobao-Green New Source Environmental Protection (Zhengzhou, Henan) powdered molecular sieve (Ca-5A); carboxymethyl cellulose was purchased from Shandong Senxin Environmental Protection Technology Co., Ltd.; the average molecular weight of polyethylene glycol was 8000, purchased from Shanghai Titan Technology Co., Ltd.; the pH of PBS buffer was 7.4, and it included the following components: Na 2 HPO 4 (Anhydrous disodium hydrogen phosphate): Shanghai Titan Technology Co., Ltd., KH 2 PO 4 (Potassium dihydrogen phosphate): Shanghai Titan Technology Co., Ltd., KCl (potassium chloride): Shanghai McLean Biochemical Technology Co., Ltd., sodium chloride (NaCl): Sinopharm Chemical Reagent Co., Ltd.

[0020] Example 1: A method for preparing a zeolite-loaded regenerated cellulose aerogel hemostatic material, comprising the following steps: (1) 3 g of carboxymethylated cellulose with a carboxymethyl substitution degree of 0.16 and 1.5 g of polyethylene glycol were dissolved in 95.5 g of 7% sodium hydroxide solution to obtain a 3% cellulose regeneration solution, and then 0.45 g of zeolite powder was added and stirred to obtain a zeolite-regenerated cellulose slurry; (2) transferring the zeolite-regenerated cellulose slurry into a mold and regenerating the fibers in an acid / alcohol coagulation bath to form a zeolite-regenerated cellulose hydrogel; (3) The zeolite-regenerated cellulose hydrogel is washed with water until neutral, and then freeze-dried at low temperature to form a zeolite-loaded regenerated cellulose aerogel hemostatic material (the ratio of zeolite to carboxymethyl cellulose is 3:20), such as Figure 1 shown.

[0021] The aerogel hemostatic material prepared in Example 1 was observed using a scanning electron microscope, and the structure was as follows: Figure 2 As shown, according to Figure 2It can be seen that the interior of the aerogel hemostatic material is a porous three-dimensional network structure, and the zeolite is evenly distributed on the fiber surface.

[0022] Example 2: A method for preparing a zeolite-loaded regenerated cellulose aerogel hemostatic material, comprising the following steps: (1) 3 g of carboxymethylated cellulose with a carboxymethyl substitution degree of 0.16 and 1.5 g of polyethylene glycol were dissolved in 95.5 g of 7% sodium hydroxide solution to obtain a 3% cellulose regeneration solution, and then 1 g of zeolite powder was added and stirred to obtain a zeolite-regenerated cellulose slurry; (2) transferring the zeolite-regenerated cellulose slurry into a mold and regenerating the fibers in an acid / alcohol coagulation bath to form a zeolite-regenerated cellulose hydrogel; (3) The zeolite-regenerated cellulose hydrogel was washed with water until neutral and freeze-dried at low temperature to form a zeolite-loaded regenerated cellulose aerogel hemostatic material (the ratio of zeolite to carboxymethyl cellulose was 1:3).

[0023] Example 3: A method for preparing a zeolite-loaded regenerated cellulose aerogel hemostatic material, comprising the following steps: (1) 3 g of carboxymethylated cellulose with a carboxymethyl substitution degree of 0.16 and 1.5 g of polyethylene glycol were dissolved in 95.5 g of 7% sodium hydroxide solution to obtain a 3% cellulose regeneration solution, and then 2 g of zeolite powder was added and stirred to obtain a zeolite-regenerated cellulose slurry; (2) transferring the zeolite-regenerated cellulose slurry into a mold and regenerating the fibers in an acid / alcohol coagulation bath to form a zeolite-regenerated cellulose hydrogel; (3) The zeolite-regenerated cellulose hydrogel was washed with water until neutral and freeze-dried at low temperature to form a zeolite-loaded regenerated cellulose aerogel hemostatic material (the ratio of zeolite to carboxymethyl cellulose was 2:3).

[0024] Performance Analysis: 1. The zeolite-loaded regenerated cellulose aerogel hemostatic material, medical cotton, and commercial Quikclot Combat Guaze prepared in Examples 1-3 were respectively subjected to in vitro coagulation performance evaluation (BCI) comparison. The specific method is as follows: Take several milliliters of fresh rabbit blood and add anticoagulant (volume ratio of 9:1), prepare a 0.2 M calcium chloride solution and let it stand. Weigh 100 mg of material at the bottom of a centrifuge tube and preheat it at 37 °C for 5 min. Then add 100 µL of anticoagulant blood and 20 µL of CaCl 2Solution, then place the beaker at 37 °C for 10 min, then add 25 mL of deionized water, and place it at 37 °C for 5 min, finally take 200 µL of the upper clear liquid, and test the absorbance (Abs) value with a visible light spectrometer (wavelength 540 nm). During the test, set up a blank control group and a positive control group (medical hemostatic cotton), and repeat the test for 6 times for each sample and take the average value; The BCI calculation formula is: ; Generally speaking, the smaller the BCI value, the better the hemostatic effect of the hemostatic material; The result is as follows Figure 3 As shown, according to Figure 3 It can be seen that the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Examples 1-3 has excellent in vitro coagulation performance.

[0025] 2. The zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Example 1, medical cotton, and commercial Quikclot Combat Guaze were compared in a blood compatibility experiment. The specific process is as follows: The citrated whole blood was centrifuged at 2000 rpm for 10 min, and the erythrocyte sediment was washed three times with PBS. Then, 200 µL of pure erythrocytes were mixed with 9.8 mL of PBS to obtain a 2 v / v% erythrocyte suspension. 10 mg of zeolite-loaded regenerated cellulose aerogel hemostatic material, Quikclot, and cotton were placed in test tubes containing 1 mL of erythrocyte suspension, and then incubated at 37 °C for 1 hour. At the same time, 50 µL of PBS and 2 wt% TritonX-100 were added to 1 mL of erythrocyte suspension as negative and positive controls, respectively. After that, all test tubes were further centrifuged at 2000 rpm for 10 min. Finally, the absorbance of the supernatant was measured at 540 nm, and six measurements were performed for each group. The formula for calculating the hemolytic ratio (HR) is: HR (%) = [(OD s -OD p ) / (OD t -OD p )] * 100%; OD s is the absorbance of the sample, OD t is the absorbance of 2 wt% TritonX-100, OD p is the absorbance of PBS; The result is as follows Figure 4 As shown, according to Figure 4It can be seen that the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Example 1 does not produce hemolysis at a concentration of 10 mg / ml.

[0026] 3. The heat release evaluation of the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Example 1 and the commercial Quiclot combat gauze during in vivo hemostasis was compared. The specific steps are as follows: Under room temperature conditions, the heat release capacity of different materials during the hemostasis process in mice was measured by infrared thermal imaging. IR imaging was performed during the hemostasis process of the mouse liver injury model, and the highest heat release temperature was recorded until the temperature almost stopped changing. The result is as follows Figure 5 As shown, according to Figure 5 It can be seen that the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Example 1 reduces the risk of thermal injury.

[0027] 4. The in vivo hemostatic performance of the zeolite-loaded regenerated cellulose aerogel hemostatic material, medical absorbent cotton, and commercial Quiclot combat gauze prepared in Example 1 was evaluated and compared. The specific steps are as follows: A rat femoral artery rupture bleeding model was used. After anesthetizing SD (Sprague-Dawley) rats, the back was fixed with the abdomen facing up, the hair at the base of the hind legs was shaved, and the base of the hind legs was disinfected with 75% medical alcohol. The femoral artery was found, and then a wound was cut at the epidermis of the femoral artery at the base of the thigh. The femoral artery was cut with surgical scissors. After it was allowed to bleed freely for 5 seconds, the floating blood on the wound was gently wiped off, and the hemostatic material was pressed on the bleeding wound, and the timing was started. The hemostatic material was gently uncovered every 30 seconds to observe whether the bleeding continued. If the wound continued to bleed, the hemostatic material was continued to be pressed until the bleeding stopped. After the hemostasis was completed, each material was weighed and the blood loss was calculated. The experiment was repeated 6 times for each sample. The result is as follows Figure 6 As shown, according to Figure 6 It can be seen that the zeolite-loaded regenerated cellulose aerogel hemostatic material prepared in Example 1 has excellent in vivo hemostatic performance.

[0028] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a zeolite-loaded regenerated cellulose aerogel hemostatic material, It is characterized in that The following steps are involved: Dissolving carboxymethyl cellulose and polyethylene glycol in an alkaline solution to obtain a cellulose regeneration solution, then adding zeolite and stirring evenly to obtain a white stable zeolite-regenerated cellulose slurry; Placing the zeolite-cellulose regenerated cellulose homogenate in an acid / alcohol coagulation bath for fiber regeneration to obtain a zeolite-regenerated cellulose hydrogel, wherein the acid / alcohol coagulation bath is a mixture of an acid solution and an alcohol, wherein the acid solution is 10% sulfuric acid by mass, the alcohol is 50% ethanol by mass, and the mass ratio of the acid solution to the alcohol is 8:92; The zeolite-regenerated cellulose hydrogel was dialyzed to neutrality and the salt was removed, and then freeze-dried to obtain the zeolite-loaded regenerated cellulose aerogel hemostatic material.

2. The method for preparing the zeolite-loaded regenerated cellulose aerogel hemostatic material according to claim 1, It is characterized in that The carboxymethyl substitution degree of the carboxymethylated cellulose is 0.10-0.

50.

3. The method for preparing the zeolite-loaded regenerated cellulose aerogel hemostatic material according to claim 1, It is characterized in that The alkaline solution is sodium hydroxide or potassium hydroxide.

4. The method for preparing the zeolite-loaded regenerated cellulose aerogel hemostatic material according to claim 1, It is characterized in that The mass concentration of carboxymethyl cellulose in the cellulose regeneration solution is 3-10%.

5. The method for preparing the zeolite-loaded regenerated cellulose aerogel hemostatic material according to claim 1, It is characterized in that The mass concentration of polyethylene glycol in the cellulose regeneration solution is 0.5-2%.

6. The method for preparing the zeolite-loaded regenerated cellulose aerogel hemostatic material according to claim 1, It is characterized in that The mass ratio of the zeolite to the carboxymethyl cellulose is 3-14:

20.

7. The method for preparing the zeolite-loaded regenerated cellulose aerogel hemostatic material according to claim 1, It is characterized in that The dialysis is performed by washing with ultrapure water or ethanol.

8. A zeolite-loaded regenerated cellulose aerogel hemostatic material, It is characterized in that It is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Devices for the delivery of molecular sieve materials for the formation of blood clots

    CN101036591A

  • Trauma hemostatic sponge and preparing method and application thereof

    CN109999216A

  • Zeolite-cellulose polyacrylamide composite hydrogel as well as preparation and application thereof

    CN115678043A

  • Porous cellulose / gelatin composite hemostatic aerogel as well as preparation method and application thereof

    CN115873299A

  • Preparation method of regenerated cellulose, regenerated cellulose and application of regenerated cellulose

    CN117050200A